[PP.14.01] ASTRAGALOSIDE IV IMPROVES LEFT VENTRICULAR DIASTOLIC DYSFUNCTION IN HYPERTENSIVE MICE BY INCREASING THE PHOSPHORYLATION OF ENDOTHELIAL NITRIC OXIDE SYNTHASE. (September 2016) - Wang, Q.; Jeong, E.; Liu, H.; Gu, L.; Dudley, S.C.; Yu, J.
Abstract : Objective: The saponin Astragaloside IV (ASI) reportedly enhances endothelial NOS (eNOS) activity by increasing the scavenging of reactive oxygen species (ROS) and NO production. We hypothesized that oxidative stress may decrease eNOS phosphorylation and result in diastolic dysfunction in DOCA-salt mice, which could be reversed by ASI treatment. Design and method: We used the deoxycorticosterone acetate (DOCA)-salt mouse model. The mice were divided into four groups; SHAM and DOCA control mice received sterile water, and the other two groups, SHAM + ASI and DOCA + ASI, received ASI treatment via an intraperitoneal injection of 0.02 mg/kg/day for 7 days. Diastolic function was assessed by echocardiography and IonOptix. The levels of eNOS monomers, dimers and phosphorylation were determined with a Western blot analysis. High performance liquid chromatography (HPLC) was used to measure the cardiac superoxide anions and biopterins. Results: DOCA mice exhibited diastolic dysfunction that was reversed after ASI treatment (E'/A': SHAM vs. DOCA 1.27 ± 0.13 vs. 0.62 ± 0.07, p < 0.001; DOCA vs. DOCA + ASI 0.62 ± 0.07 vs. 1.27 ± 0.29, p = 0.002. E/E': SHAM vs. DOCA 23.90 ± 4.58 vs. 38.83 ± 4.37, p = 0.001; DOCA vs. DOCA + ASI 23.90 ± 4.58 vs. 25.28 ± 3.40, p = 0.001). Isolated myocytes from the DOCA-salt mice demonstrated impaired relaxation, diastolic sarcomere length and re-lengthening (relaxation constant), which were restored by ASI treatment. The DOCA mice showed increased superoxide production and reduced NO production, which were alleviated by ASI (2HO-ET level: DOCA vs. DOCA + ASI 0.36 ± 0.19 mol/mg tissue vs. 0.20 ± 0.05 μmol/mg tissue, p = 0.049. nitrite/nitrate content: DOCA vs. DOCA + ASI 2.58 ± 0.49 mmol/mg protein vs. 3.33 ± 0.30 mmol/mg protein, p = 0.04). Our results showed that the levels of eNOS dimers, eNOS-S1177 and eNOS-T495 were significantly decreased in the DOCA-salt mice compared with the SHAM mice. The level of eNOS-S1177 was increased in the DOCA + ASI mice compared with the untreated DOCA-salt mice (p = 0.026); however, ASI did not affect the phosphorylation of eNOS-T495. MyBP-C S-glutathionylation increased after ASI treatment in the DOCA + ASI mice compared with the DOCA-salt hypertensive mice (p = 0.046). Conclusions: The decrease in eNOS dimerization and phosphorylation correlated with diastolic dysfunction, which was reversed by ASI in DOCA-salt mice. The anti-oxidative effects of ASI on MyBP-C glutathionylation and eNOS phosphorylation preserved cardiac relaxation.